Food Habit of Seluang Batu (Paracrossochilus vittatus Boulenger 1894) in Mentuka River Sekadau Districts West Kalimantan Province - Pratiwi, Diah; Setyawati, Tri Rima; Yanti, Ari Hepi (Jurnal ILMU DASAR, 2020)
Seluang batu (Paracrossochilus vittatus) is one of the Borneo endemic fish from Cyprinidae Family that live in high stream water. The aim of this study was to know the food habit and niche breadth of seluang batu in Mentuka River. This study was conducted 3 months from November 2016 to January 2017. The sampling method used in this research was purposive random sampling. Seluang batu was taken from three stations in the Mentuka River using trap nets. The fish was measured in length and weight, then dissected to find out the type of food in the stomach. Food analysis was determined using index of preponderance and the niche breadth using Smith’s index. The results showed that seluang batu in Mentuka River including herbivore because they eat microalgae, namely Synedra was main food. Nice breadth of seluang batu for peryphiton was 0.71 meanwhile plankton was 0.20. Most of peryphiton and plankton in Mentuka River are Bacillariophyceae. The Mentuka River environtment supported the life of seluang batu and their natural food, namely the temperature about 26-28 ̊C, current speed was about 1-2,6 m/s, pH was about 6,8-7,3, dissolved oxygen was about 6,1-7 mg/L and free CO2 was 3,9-5,0 mg/L. Keywords: food habit, Paracrossochilus vittatus, periphyton, plankton.